Continuous reduction of tellurite to recoverable tellurium nanoparticles using an upflow anaerobic sludge bed (UASB) reactor. (1st January 2017) - Ramos-Ruiz, Adriana; Sesma-Martin, Juan; Sierra-Alvarez, Reyes; Field, Jim A.
Abstract: According to the U.S. Department of Energy and the European Union, tellurium is a critical element needed for energy and defense technology. Thus methods are needed to recover tellurium from waste streams. The objectives of this study was to determine the feasibility of utilizing upflow anaerobic sludge bed (UASB) reactors to convert toxic tellurite (Te IV ) oxyanions to non-toxic insoluble elemental tellurium (Te 0 ) nanoparticles (NP) that are amendable to separation from aqueous effluents. The reactors were supplied with ethanol as the electron donating substrate to promote the biological reduction of Te IV . One reactor was additionally amended with the redox mediating flavonoid compound, riboflavin (RF), with the goal of enhancing the bioreduction of Te IV . Its performance was compared to a control reactor lacking RF. The continuous formation of Te 0 NPs using the UASB reactors was found to be feasible and remarkably improved by the addition of RF. The presence of this flavonoid was previously shown to enhance the conversion rate of Te IV by approximately 11-fold. In this study, we demonstrated that this was associated with the added benefit of reducing the toxic impact of Te IV towards the methanogenic consortium in the UASB and thus enabled a 4.7-fold higher conversion rate of the chemical oxygen demand. Taken as a whole, this work demonstrates the potential of a methanogenic granular sludge to be applied as a bioreactor technology producing recoverable Te 0 NPs in a continuous fashion. Graphical abstract: Highlights: A continuous anaerobic bioreactor converted Te IV to elemental Te 0 nanoparticles. Te IV reduction rates depended on biomass and Te IV concentrations. Ethanol used as an electron donating substrate promoted Te IV reduction. Riboflavin used as redox mediator greatly improved Te IV reduction. Riboflavin markedly lowered Te IV toxicity to chemical oxygen demand removal.